The agility demands of Australian football: a notational analysis - Rayner, R.; Young, W. B.; Talpey, S. W. (International Journal of Performance Analysis in Sport, 2022)
Agility is essential to success in Australian football (AF). However, the nature of agility events in competition is currently unknown. This study analysed in-game 1v1 agility events to identify the movement and cognitive demands of agility in elite AF. The study described the technique, the angle of change of direction (COD), and the approach speed. Cognitive demands were inferred by recording inter-athlete position and deceptive manoeuvres. Findings revealed sidestepping to be commonly used for both attacking and defending athletes. However, attacking athletes were substantially more likely to use the sidestep technique than their defending counterparts (74% vs 39% of the time). Analysis of movement speeds indicated a preference for submaximal approaches. Further, the movement technique was varied, with the angle of directional change particularly diverse. Overall, the notational analysis indicates a need for agility training and testing that reflects in-game agility demands. To achieve this, training and testing must allow for submaximal movement speeds, context-specific techniques, and the use of deceptive manoeuvres. Field-based or subjective assessment methods are proposed as viable testing alternatives. Further, the effectiveness of recorded deceptive actions suggests that athletes should be provided with training opportunities to practice fake disposals and fake CODs.